The Knowledge of Viticulture in Hittite Anatolia: An Interdisciplinary Approach - Corti, Carlo (Die Welt des Orients, 2018)
Wine and viticulture played a significant role in Hittite Anatolia of the second millennium BC. This assumption is demonstrated by the rich terminology in Hittite and other Anatolian languages that involves not only the designation of different varieties of wine and derivatives, but also the technical lexicon of the grapevine and its parts. Work in the vineyard must also have been highly specialized because we know of the existence of a specific category of workers: the “vine dressers”. This contribution offers new data on the botany of the grapevine and on its reproduction and cultivation techniques thanks both to sources until now neglected and to the interpretation of several termini technici from a botanical perspective. Furthermore, it presents an overview of the main agricultural areas chosen by the Hittites as suitable for vine cultivation.